Family, Religion and Law - Cultural Encounters in Europe - Rohe, Mathias; Shah, Prakash; Foblets, Marie-Claire (Ashgate Publishing Group, 2014)
This collection discusses how official legal systems do and should respond to the reality of a plurality of family types and origins within their jurisdictions. It further examines the challenges that arise for practitioners, including lawyers and judges, when faced with such plurality. Focussing on empirical research, the volume presents legal and sociological data of unprecedented comparative depth. It also includes a discussion of how members of minority families respond to the need to organise their legal relationships, and to resolve their disputes in the shadow of official legal systems which differ from those of their familial and communal traditions. The work invites reflection, and demonstrates the urgency and complexity of the questions regarding the search for justice in the field of family life in Europe today. © Prakash Shah with Marie-Claire Foblets and Mathias Rohe, and the contributors 2014. All rights reserved.
UnivIS-Import:2015-05-08:Pub.2014.rw.recht.IZZ.LZZA.family